Federated States of Micronesia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Federated States of Micronesia. (IMF Staff Country Reports; Country Report ;, 2021)
The COVID-19 pandemic and related containment measures have put severe strains on the economy. The economic policy response has been strong and generally appropriate, helping counter the negative effects of the pandemic. Nevertheless, as the international borders remain shut, the economic contraction is likely to deepen in FY2021. A slow recovery is expected for FY2022 driven by a gradual border reopening. The FSM is facing significant medium-term uncertainty, owing to the possible expiration of grants and other assistance provided under the Compact Agreement with the United States. The FSM is also highly vulnerable to climate change-induced natural disasters.